2007
DOI: 10.1021/la063640+
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acids Influence “Solid” Phase Formation in Models of Stratum Corneum Intercellular Membranes

Abstract: Stacked intercellular lipid membranes in the uppermost epidermal layer, the stratum corneum (SC), are responsible for skin's barrier function. These membranes are unique in composition, the major lipids being ceramides (Cer), cholesterol, and free fatty acids (FFA) in approximately equimolar proportions. Notably, SC lipids include chains much longer than those of most biological membranes. Previously we showed that Cer's small hydrophilic headgroup enabled SC model membranes composed of bovine brain ceramide (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
61
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(74 citation statements)
references
References 52 publications
(134 reference statements)
8
61
0
3
Order By: Relevance
“…S4B), similar to a neat isotropic solution of OMTS. From the present analysis, we are not able to pinpoint the location of fast isotropic solvent molecules, and we cannot distinguish between cases when the solvent is present in isotropic fluid domains within SC (11,(41)(42)(43)(44) and when it is present in an excess solution. However, we combine the studies of the molecular dynamics of the solvent molecules with an analysis of how the added solvent influences the molecular dynamics in SC lipid and protein components.…”
Section: Pt Ssnmr To Monitor Molecular Conformation and Dynamics Inmentioning
confidence: 70%
See 1 more Smart Citation
“…S4B), similar to a neat isotropic solution of OMTS. From the present analysis, we are not able to pinpoint the location of fast isotropic solvent molecules, and we cannot distinguish between cases when the solvent is present in isotropic fluid domains within SC (11,(41)(42)(43)(44) and when it is present in an excess solution. However, we combine the studies of the molecular dynamics of the solvent molecules with an analysis of how the added solvent influences the molecular dynamics in SC lipid and protein components.…”
Section: Pt Ssnmr To Monitor Molecular Conformation and Dynamics Inmentioning
confidence: 70%
“…Adding more polar solvents to SC gradually leads to swelling of the corneocytes, and the solvent dynamics approaches that of the neat liquid. The addition of apolar solvents leads to an increased amount of fluid SC lipids, which also shows the characteristics of an isotropic fluid (11,(41)(42)(43). At high concentrations SC will be saturated with the solvent.…”
Section: Discussionmentioning
confidence: 99%
“…The uniqueness of the organization is strongly dependent on the composition of the lipid [16] and governs the permeability and barrier properties of the SC [23,39]. …”
Section: Stratum Corneummentioning
confidence: 99%
“…Optimum percentages of all three major classes of SC lipid are important for the formation of orthorhombic lateral packing [4,6,8,19,20,22,39,48,52,53]. A study by Norlén et al [27] indicated that as one goes deeper into the SC layers, the amount of FFA decreases, which results in an increase in transepidermal water loss (TEWL).…”
Section: Stratum Corneummentioning
confidence: 99%
“…Subtle changes in the permeability properties of the membranes participating in the barrier can be caused by lipid compositional changes. For example, it has been reported that the characteristic FFA composition of the stratum corneum membranes is a very important factor in promoting hydrocarbon chain mixing, defi ning lipid mixing properties and membrane stability ( 55,67 ). Similarly, the increased apparent pH detected in the stratum corneum of ACBP Ϫ / Ϫ mice may also modulate the stability of the membranes by enhancing ionization of the FAs.…”
Section: Acbp ؊ / ؊ Mice Display Impaired Epidermal Permeability Barrmentioning
confidence: 99%